The Individual and Contextual Factors of Precarious Employee Status of Youth Workers in Indonesia 2024: Application Multilevel Binary Logistic Regression - Mandy, Arya Samuel; ., Sugiarto (Politeknik Statistika STIS, 2025)
Human resources are a strategic component for countries in achieving developmentgoals and promoting progress. Among age groups, youth play an important role as drivers of acountry's development. However, the challenge of obtaining decent work is a serious problemthat causes many youth people in Indonesia to be forced into precarious employment. In the lastfour years, the Precarious Employment Rate (PER) of youth people in Indonesia in 2024 hasincreased dramatically compared to the previous year, even becoming the highest among all agegroups. This study aims to determine the general picture and analyze the individual andcontextual factors that influence the status of precarious employees among youth workers inIndonesia. The analysis method used is multilevel binary logistic regression. The results of thestudy show that 85.97 percent of youth workers in Indonesia have precarious employee status.The analysis shows that individual factors such as gender, marital status, education level,participation in training, regional classification, employment sector, labor union membership,and contextual factors such as the provincial minimum wage have a significant effect on theprecarious employee status of youth workers in Indonesia in 2024.